2016
DOI: 10.1155/2016/2753429
|View full text |Cite
|
Sign up to set email alerts
|

Carious Exposure versus Mechanical Exposure for MTA Pulpotomy in Primary Teeth

Abstract: Introduction. The etiology of exposure determines pulpal response, making it crucial to distinguish between mechanical and carious exposure. This study clinically and radiographically evaluated the success of MTA pulpotomies conducted to treat carious and mechanical pulp exposure. Materials and Methods. This study was conducted with 50 mandibular primary molar teeth. Teeth were divided into 2 groups according to status of the exposure site, with teeth surrounded by carious dentin placed in a carious exposure g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…PCO is a common radiographic finding in pulpotomized teeth. Although some investigators [ 51 ] have considered PCO to constitute a radiographic failure because it demonstrates a deviation from normal pulp, most investigators [ 46 , 52 54 ] agree to the contrary, since PCO results from the extensive activity of odontoblast-like cells that suggests retained vitality. In the present study, PCO was not regarded as a failure and was the most commonly observed radiographic finding.…”
Section: Discussionmentioning
confidence: 99%
“…PCO is a common radiographic finding in pulpotomized teeth. Although some investigators [ 51 ] have considered PCO to constitute a radiographic failure because it demonstrates a deviation from normal pulp, most investigators [ 46 , 52 54 ] agree to the contrary, since PCO results from the extensive activity of odontoblast-like cells that suggests retained vitality. In the present study, PCO was not regarded as a failure and was the most commonly observed radiographic finding.…”
Section: Discussionmentioning
confidence: 99%
“…ProRoot MTA and formocresol were not significantly different in the success rates of the materials in carious and mechanical exposures (Ozdemir et al . , Çelik & Sarı ). However, calcium hydroxide had a significantly higher success rate in sound, intact primary teeth compared to those that were cariously exposed.…”
Section: Vital Pulp Therapiesmentioning
confidence: 99%
“…In deep decayed temporary molars, it is impossible to accurately assess the pulpal inflammatory status and its severity, both of which are key factors for assessing prognosis in primary teeth. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%